Ground Water Quality Assessment Using Multi‐Rectangular Diagrams - Ahmad, Niaz; Sen, Zekai; Ahmad, Manzoor (Wiley, 2003)
Abstract A new graphical technique is proposed here for classifying chemical analyses of ground water. In this technique, a diagram is constructed using rectangular coordinates. The new diagram, called a multi‐rectangular diagram (MRD), uses adjacent multi‐rectangles in which each rectangle represents a specific ground water type. This new diagram has the capability to accommodate a large number of data sets. MRDs have been used to classify chemical analyses of ground water in the Chaj Doab area of Pakistan to illustrate this new approach. Using this graphical method, the differentiated ground water types are calcium bicarbonate, magnesium bicarbonate, sodium bicarbonate, and sodium sulfate. Sodium bicarbonate emerges as the most abundant ground water type. MRDs also offer a visual display of the Chebotarev sequence of ground water quality evolution.
Keywords: Quality Control; Soil; Models, Statistical; Water Supply; Soil Pollutants; Water Pollutants; Environmental Monitoring